Credit card knowledge, social motivation, and credit card misuse among college students: Examining the information-motivation-behavioral skills model. Issue 5 (3rd July 2017) - Limbu, Yam B.
Abstract : Purpose: By applying the information-motivation-behavioral (IMB) skills model, the purpose of this paper is to examine the direct and indirect effects of credit card knowledge and social motivation on credit card misuse behavior mediated through credit card self-efficacy among college students in the USA. Design/methodology/approach: A sample of 427 participants was surveyed. Structural equation modeling was used to assess the hypothesized model. Findings: Credit card knowledge and social motivation were inversely associated with credit card misuse mediated through credit card self-efficacy. Credit card knowledge had a direct negative relationship with credit card misuse. The results confirm the theoretical relationships in the IMB model. Practical implications: The results offer several implications for bank marketers and policy makers. The IMB model could be used to predict credit card abuse among college students; credit card literacy programs should incorporate strategies that can enhance students' knowledge, social motivation, and behavioral skills with regard to responsible use of credit cards. Originality/value: This study is unique in that it applies the IMB model to examine predictors of credit card misuse among college students.